2019
DOI: 10.1002/adma.201900763
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hybrid‐Layered Organic Phototransistor Enables Efficient Intermolecular Charge Transfer and Carrier Transport for Ultrasensitive Photodetection

Abstract: Scheme 1. a,b) Schematic structures of a layered OPT (a) and a hybrid OPT (b), and c) the general design of the HL-OPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 51 publications
(63 reference statements)
6
83
0
Order By: Relevance
“…Further, 2 mg/mL and 5 mg/mL contents could also realize responsivity of 435.6 mA/W and 382.4 mA/W, respectively. By comparing the influence of 1 mW/cm 2 and 8 mW/cm 2 light intensities on the responsivity in detail, we obtained similar results to previous reports [13,14,15]; the value of responsivity decreased with the increase of light intensity, which indicated that the phototransistor fabricated by one-step spin-coating using the vertical phase separation method had good light detection performance. Figure 5d–f show the relationship between the detectivity of devices with gate voltage and light intensity, and it is clearly seen that the detectivity of the device reached the relatively large value of about 3.39 × 10 10 Jones.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Further, 2 mg/mL and 5 mg/mL contents could also realize responsivity of 435.6 mA/W and 382.4 mA/W, respectively. By comparing the influence of 1 mW/cm 2 and 8 mW/cm 2 light intensities on the responsivity in detail, we obtained similar results to previous reports [13,14,15]; the value of responsivity decreased with the increase of light intensity, which indicated that the phototransistor fabricated by one-step spin-coating using the vertical phase separation method had good light detection performance. Figure 5d–f show the relationship between the detectivity of devices with gate voltage and light intensity, and it is clearly seen that the detectivity of the device reached the relatively large value of about 3.39 × 10 10 Jones.…”
Section: Resultssupporting
confidence: 88%
“…Compared to conventional photodiodes, phototransistors are controllable devices whose carrier density in the channel region can be tuned by the gate electrode, and therefore act as an in-built amplifier for enhancing the signal to noise ratio [2,11,12]. In recent years, investigations of phototransistors have mainly focused on the device structure design, fabrication process optimization, and material synthesis and selection, where the basic OTFT platforms are based on multiple layer structures [13,14,15,16]. The functional layers in the OTFTs, including electrodes, the dielectric layer, and semiconducting layers, are typically processed by thin film deposition techniques with a stacked layer-by-layer geometry [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, two published works have showed that forming an insulating wide-bandgap layer at the interface between the perovskite and charge transporting layers could effectively reduce the interfacial nonradiative losses 50,51 . There is also an example that demonstrates how to tackle interfacial losses by adding a layer of electron-blocking MoO 3 in-between the light absorber and the phototransistor 52 . We note that even in a type-II HJ-based perovskite quantum-dot/organic phototransistor, the photocarrier transfer could still benefit from the insulating ligands formed on the surfaces of the quantum dots 53 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 1–4 ] By virtue of the additional gate terminal, organic phototransistors (OPTs), compared with their two‐terminal counterparts, enable easier modulation during light detection without issues such as increasing noise. [ 2,5 ] The photoresponsivity and sensitivity of the OPTs are continuously improved, while one outstanding issue is that these devices still suffer from slow response speed, which is detrimental to their application in emerging fields such as optical imaging and communication. [ 6,7 ] An essential approach for constructing OPTs is to form the planar heterojunctions, which is a critical structure for the separation of the strongly bound photogenerated excitons, [ 8,9 ] while the exciton diffusion still plays a critical role in the response speed of the OPTs.…”
Section: Introductionmentioning
confidence: 99%